If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 2) = 323 Reorder the terms: x(2 + x) = 323 (2 * x + x * x) = 323 (2x + x2) = 323 Solving 2x + x2 = 323 Solving for variable 'x'. Reorder the terms: -323 + 2x + x2 = 323 + -323 Combine like terms: 323 + -323 = 0 -323 + 2x + x2 = 0 Factor a trinomial. (-19 + -1x)(17 + -1x) = 0Subproblem 1
Set the factor '(-19 + -1x)' equal to zero and attempt to solve: Simplifying -19 + -1x = 0 Solving -19 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + -1x = 0 + 19 Combine like terms: -19 + 19 = 0 0 + -1x = 0 + 19 -1x = 0 + 19 Combine like terms: 0 + 19 = 19 -1x = 19 Divide each side by '-1'. x = -19 Simplifying x = -19Subproblem 2
Set the factor '(17 + -1x)' equal to zero and attempt to solve: Simplifying 17 + -1x = 0 Solving 17 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + -1x = 0 + -17 Combine like terms: 17 + -17 = 0 0 + -1x = 0 + -17 -1x = 0 + -17 Combine like terms: 0 + -17 = -17 -1x = -17 Divide each side by '-1'. x = 17 Simplifying x = 17Solution
x = {-19, 17}
| -2+n/4=-4 | | -2(8)+8y=-16 | | 2z=-16z+2(13z-4) | | ln(6x+1)-1lnx=2 | | 71-2=34x+23 | | -3(-12+17r)=4(3-12r) | | 8m+7=71 | | 4x^3+12x^2-7x-30=0 | | -2*0+8y=-16 | | 4(s+9)+4=6s | | 6(-12t+19)+19t=-20t-18 | | 9m+6n-3m+10n= | | 7x+8*0=56 | | 3x=27/9 | | 6y-11=43 | | 20+5+19c=-6(-5c+19)-15 | | 7*0+8y=56 | | 6p+3=5+5p | | -4x-7*0=28 | | 20a+17b+5c+5c-6b-5a= | | -6(-4+3x)=24 | | 3n-7(6n+8)=26+2n | | -6(-13w+18)-15=-9(-10w+3) | | r(x)=x^2+5x+6 | | -5x+3=33+5x | | 2x+12+7x=3x+93x | | 4(1a+1)=4a+8 | | ln(6x+1)-lnx=2 | | X*0.12=0.60 | | y-13=-12 | | -4*0-7y=28 | | aeg=10solveg |